A GLOBAL PERSPECTIVE OF SOCIAL ECONOMIC LAW: A COMPARATIVE APPROACH AND POLICY ANALYSIS - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The global perspective of social economy law reflects the various approaches and policies implemented by countries around the world to achieve economic and social well-being. Using a comparative approach, this research explores the significant differences in legal regulation, government intervention, and welfare models implemented in Europe, the United States, and Asia. Policy analyses show that the success and effectiveness of the various models are strongly influenced by each country's historical, cultural and structural context. Case studies of the Nordic countries and Singapore illustrate how different social welfare strategies can result in reduced poverty and inequality, while promoting economic growth. By studying and comparing these approaches, policymakers can develop more effective and adaptive solutions to economic and social challenges in different local contexts.